Molecular origins of the multi-donor strategy in inducing bathochromic shifts and enlarging Stokes shifts of fluorescent proteins. Issue 26 (21st June 2022) - Wu, Xia; Tan, Davin; Qiao, Qinglong; Yin, Wenting; Xu, Zhaochao; Liu, Xiaogang
Abstract : We rationalize a multi-donor strategy that leads to desirable bathochromic shifts and large Stokes shifts with minimal structural changes for creating long-wavelength fluorescent proteins (LWFPs). Abstract : Long-wavelength fluorescent proteins (LWFPs) and LWFP-based sensors are indispensable tools for bioimaging and biosensing applications. However, it remains challenging to develop LWFPs with outstanding brightness and/or sensitivities, largely due to the lack of simple and effective molecular design strategies. Herein, we rationalized the molecular origins of a multi-donor strategy that affords significant bathochromic shifts and large Stokes shifts with minimal structural changes in the resulting protein fluorophores. We analyzed three key factors that affect the spectral properties of these fluorophores, including the (1) substituent position, (2) electron-donating strength, and (3) number of electron-donating groups. We further demonstrated that this simple design strategy is generalizable to various fluorophore families. We expect that this work can provide rational guidelines for developing fluorescent proteins (and small-molecule fluorophores) with long emission wavelengths and large Stokes shifts.